Scalable one-step electrochemical deposition of nanoporous amorphous S-doped NiFe2O4/Ni3Fe composite films as highly efficient electrocatalysts for oxygen evolution with ultrahigh stability. Issue 4 (5th January 2018) - Gao, M. Y.; Zeng, J. R.; Zhang, Q. B.; Yang, C.; Li, X. T.; Hua, Y. X.; Xu, C. Y.
Abstract : Self-supported 3D nanoporous amorphous S-doped NiFe2 O4 /Ni3 Fe composite films grown on nickel wire were fabricated via a facile and scalable one-step electrochemical deposition route in ethaline and developed as highly active and robustly stable electrocatalysts for OER in alkaline media. Abstract : The rational design of noble metal-free electrocatalysts that are highly active, robustly stable, and capable of delivering large current densities (>500 mA cm −2 ) at low applied potentials (<300 mV), in particular for oxygen evolution reaction (OER), is critical for practical use in electro-driven water-splitting devices. Herein, we report a facile scalable and one-step electrochemical deposition approach for the development of a self-supported 3D nanoporous S-doped amorphous NiFe2 O4 /Ni3 Fe composite electrode with outstanding OER electrocatalytic activity and robust durability in alkaline media. Benefiting from the 3D nanoporous architectures and their in situ growth on a highly conductive substrate, the novel S-doped NiFe2 O4 /Ni3 Fe composite electrode offers an ideal platform for fast electron transport and efficient mass transport. It also provides abundant active surface area as well as accessible active sites for a catalytic reaction. Impressively, the S-doped composite electrode displays superior OER activity in 1.0 M KOH that compares favorably with the state-of-the-art RuO2 catalyst. Low overpotentials of 260 and 285 mV ( iR corrected) are required to reach long-term stable current densities of 100 and 500 mA cm −2 for OER, respectively. The electrolyzer cell obtained by pairing this S-doped composite electrode as an anode with a Ni–Mo based cathode for overall water-splitting works efficiently in both 1.0 M (1.52 V for 10 mA cm −2 and 1.79 V for 100 mA cm −2 ) and 30 wt% KOH (1.69 V for 100 mA cm −2 ) solutions, with long durability for over 220 h. Such catalyst couple exhibits superior catalytic performance and holds great promise for potential application in electrochemical water splitting.